Interwar Kražiai in Oral Narration - Gedvilaitė, Emilija; Kvietkuvienė, Emilija (Lietuvos istorijos studijos, 2025)
The article reveals a picture of Kražiai, a minor town, during the interwar years while covering the range from the stories of homes and their families to the staple food which found its way onto the dinner table and descriptions of the daily worn clothes. The article names the cultures, public institutions and organizations which were active in the town at the time and introduces the mundane as well as more memorable occupations of the residents, including the commonly practiced crafts. The story is built on memories of Kražiai town residents, including those narrators who observed the events in person, and also stories of interwar-time witnesses, as memorized and recounted by their offspring. The memories were collected during an expedition an oral history expedition which took place in Kražiai in 2024, which was organized by Kražiai Žygimantas Liauksminas Gymnasium and Vilnius University Faculty of History, and which involved Vilnius University and Kražiai Gymnasium students. The collected materials were generalized and rendered by a student of Kražiai Gymnasium. Along with the fascinating and valuable material, this article serves as a witness of the interest of the local gymnasium and its students in the history of the land, along with efforts to register and explore this history.